If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(6 + -3x) + -8(X + -24) = -7X + X (6 * 4 + -3x * 4) + -8(X + -24) = -7X + X (24 + -12x) + -8(X + -24) = -7X + X Reorder the terms: 24 + -12x + -8(-24 + X) = -7X + X 24 + -12x + (-24 * -8 + X * -8) = -7X + X 24 + -12x + (192 + -8X) = -7X + X Reorder the terms: 24 + 192 + -8X + -12x = -7X + X Combine like terms: 24 + 192 = 216 216 + -8X + -12x = -7X + X Combine like terms: -7X + X = -6X 216 + -8X + -12x = -6X Solving 216 + -8X + -12x = -6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6X' to each side of the equation. 216 + -8X + 6X + -12x = -6X + 6X Combine like terms: -8X + 6X = -2X 216 + -2X + -12x = -6X + 6X Combine like terms: -6X + 6X = 0 216 + -2X + -12x = 0 Add '-216' to each side of the equation. 216 + -2X + -216 + -12x = 0 + -216 Reorder the terms: 216 + -216 + -2X + -12x = 0 + -216 Combine like terms: 216 + -216 = 0 0 + -2X + -12x = 0 + -216 -2X + -12x = 0 + -216 Combine like terms: 0 + -216 = -216 -2X + -12x = -216 Add '12x' to each side of the equation. -2X + -12x + 12x = -216 + 12x Combine like terms: -12x + 12x = 0 -2X + 0 = -216 + 12x -2X = -216 + 12x Divide each side by '-2'. X = 108 + -6x Simplifying X = 108 + -6x
| 33+15x=3x-x+4x | | 17+5y+9=3y+5y+9 | | 6x-15+2x=7 | | X-4=x+1 | | 4x+5=2x-15 | | -5t+10=8t-9 | | 4z+2-z=9+2z+9 | | 7.6-5x+5.5=1.6 | | 10+4x+6x=-1 | | -7x-2=40 | | 2b-3=18 | | 3(5-a)-23=21a-4(2+6a) | | X+28=49 | | 4(x-5)=3(x-2) | | 2c+25=100 | | 2.32x+7.41=-4.78x-8.21 | | -44=6x+7x+8 | | 6-(2p+5)=6[(2p-5)-(p-3)] | | 6(5v+2)=-20-2v | | 3a+15=26 | | 6x+2=3x-7 | | X-49=28 | | 5x+26=41 | | 19x-3=11x-19 | | 19x-3=11x-19 | | 4(v-7)+8(8+7v)=36 | | 3x-7+2-5x=15 | | 16.66d+.66=.25d-.50 | | 48=7x+2x+3 | | p+17=-9 | | 8=17-a | | -5x+10=-10 |